Clinical vs. exclusively online sperm donors: what's the difference?. (1st January 2019) - Whyte, Stephen
ABSTRACT: Background/objectives : As the growth of the internet and commercial connection websites increasingly facilitates sperm donation outside of clinical (formal) settings, studies looking into informal (online) donor psychology and behaviour are both extremely warranted and currently under-researched. This study's aim was to identify key differences between informal donor males with a history of clinical donation, and those who exclusively participate in the informal market. Methods : The study utilises ( N = 112) current informal sperm donors' demographics and personality traits taken from registered members of the connection website PrideAngel (Nov–Dec 2016). This study conducts probit multivariate and interaction analysis of socioeconomic and personality factors to explore key differences in males who have chosen to exclusively donate through connection websites and those with a clinical history. Results : Results from this sample show that exclusively informal donors are more likely to be in some form of committed relationship. Exclusively informal males are also more likely to identify as a sexuality other than heterosexual (e.g. gay, bisexual or asexual). Also, exclusively informal participants exhibit higher average scores for the personality trait agreeableness. Conclusions : Overall, this study demonstrates key differences in the relationship status, sexuality and personality traits of a new and burgeoning group of males and their reproductive psychology and behaviour.